From multi-hazard early warning systems (MHEWS) to all-vulnerability warning systems (AVWS) - Ilan Kelman; Carina J. Fearnley (iScience, 2025)
Summary: Science, policy, and practice have long accepted that disasters occur due to vulnerabilities rather than hazards, yet approaches to warnings still tend to be hazard-focused. Multi-hazard early warning systems (MHEWS) are meant to provide warnings for many hazards, whether sequential, simultaneous, or cumulative, and even if ostensibly independent. Despite their advantages, MHEWS display the same inherent limitation as most warning systems: they focus on hazards, without sufficient attention given to vulnerabilities. This paper aims to explain and overcome this limitation of hazard-focused warnings and warning systems. Following discussion of the ethos behind, advantages of, and limitations regarding MHEWS including with respect to the United Nation’s “Early Warnings for All” initiative, this article proposes a complement to MHEWS: All-Vulnerability Warning Systems (AVWS). The implications of and further work for implementing AVWS are discussed, highlighting the vision that warning systems as social processes should:(1) Across different people, address vulnerabilities conferring widely varying experiences to the same hazard.(2) For the same people, address vulnerabilities conferring similar difficulties to different hazards.